PENGGUNAAN ALAT PELINDUNG DIRI TERHADAP PENCEGAHAN PENYAKIT CACING KULIT (STUDI KASUS: PEKERJAAN KAMPUS UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA DI KECAMATAN TANGKETADA) - Yanti, Yanti (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
The dangers of both physical and biological hazards work environment need to be controlled in such a way that created a safe, healthy and comfortable work environment. The dangers of the work environment such as occupational illness, occupational illness and occupational accidents. There are various ways to overthrow such hazards such as technique control, administrative control and personal protective equipment. Workers already use personal protective equipment (helmets, goggles, cotton gloves, work clothes and safety shoes but still exposed to skin worm disease. Because the part that often affected by skin worm disease is the part of the hand then tried to be controlled with personal protective equipment in the form of gloves. The purpose of this research is to know how the effectiveness of the use of personal protective equipment for the prevention of skin worm disease in the work of USN Kolaka campus in Tangketada subdistrict. This type of research is a quantitative descriptive describing or describing a state of sewage work and gutter and its relation to skin worm disease. Existing secondary data is collected and tested for its effectiveness on the use of additional personal protective equipment. The results of the study using the Chi-Square test manually that the result is χ2 (count) 2.7 smaller than χ ² (table) (χ ² 0.05 | 1 |) amounting to 3,481 then early hypothesis was accepted that the use of personal protective equipment was ineffective against the prevention of Skin worm disease in the excavation work and hoarding USN Kolaka campus in Tangketada subdistrict.